Targeting the hERG1/β1 integrin complex in lipid rafts potentiates statins anti-cancer activity in pancreatic cancer - Claudia Duranti; Jessica Iorio; Valeria Manganelli; Giacomo Bagni; Rossella Colasurdo; Tiziano Lottini; Michele Martinelli; Chiara Capitani; Giulia Boso; Franco Nicolas D’Alessandro; Maurizio Sorice; Andrea Becchetti; et al. (Cell Death Discovery)
Abstract Plasma membrane macromolecular complexes function as signaling hubs that regulate cell behavior, which is particularly relevant in cancer. Our study provides evidence that the complex formed by the hERG1 potassium channel and the β1 subunit of integrin receptors preferentially localizes in Lipid Rafts (LRs) in Pancreatic Ductal Adenocarcinoma (PDAC) cell lines and primary samples. The complex recruits the p85 subunit of phosphatidyl-inositol-3-kinase (PI3K), activating phosphoinositide metabolism and triggering an intracellular signaling pathway centered on Akt. This pathway ultimately affects cancer cell proliferation through cyclins and p21, and cell migration through the small GTPase Rac-1 and f-actin organization. The hERG1/β1 integrin complex in LRs can be dissociated and the downstream signaling pathway can be inhibited by either disrupting LRs through methyl-beta-cyclodextrin (MβCD) or inhibiting cholesterol synthesis by statins. Treatment with a single chain bispecific antibody—scDb-hERG1-β1—specifically targeting the complex significantly potentiates the effects of both MβCD and statins on intracellular signaling. Consequently, these treatments decrease PDAC cell proliferation and motility in vitro. From a pharmacological perspective, different statins produce anti-neoplastic effects in synergy with scDb-hERG1-β1. Such combination also enhances tumor sensitivity to chemotherapeutic drugs, such as gemcitabine and oxaliplatin. The efficacy of these combination treatments depends on the amount of the hERG1/β1 integrin complex present on the plasma membrane of cancer cells. Finally, the combined treatment with statins and scDb-hERG1-β1 significantly reduces tumor growth and improves survival in vivo, in a preclinical mouse model. These results suggest that the combination of scDb-hERG1-β1 and statins represent a potential novel strategy for treating PDAC patients.